Implementasi Multi-Mikrokontroller pada Mobile Robot sebagai Pengendali Kecepatan dengan Kendali PID - Saragih, Agus Sehatman (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2014)
Mobile robot navigation system with wall follower method as the motion reference, usingultrasonic sensors in tracking rooms and avoid obstacles / hindrances. The number of ultrasonicsensors are used, can facilitate the robot navigation. PID control is used to control the motor speedmobile robot. Rotary encoder is a sensor that can be used to calculate the rotational speed of theactuator (dc motors).Microcontroller as the main control has the workload to perform distance calculations(ultrasonic sensor) at the same speed calculation actuators / motors (rotary encoder). The calculationprocess in real-time and continuous. Application of multi-microcontroller applied to reduce theworkload of the main microcontroller / Master. Slave microcontroller is used for the implementationof PID control.Motor rotational speed by measuring the duty cycle motors pulse are less effective, it can beseen from the values of speed on each trial setting point analog PWM. Motor speed conversion canuse another method such as a frequency-to-voltage conversion and use a voltage analog to digitalconverter (ADC) to get the present value (PV), so the data 8-bit digital-to-analog converter (DAC)directly compared with the 8-bit data analog to digital converter (ADC).